An Analysis of Code-Mixing in The Indah G Show YouTube Channel - Aryanti, Nia Putri; Dieni, Novita Al Ihyak (Universitas 17 Agustus 1945 Semarang, 2024)
The common social media platform YouTube has encountered an increase in the practice of code-mixing, which is the use of two or more languages in one conversation. Understanding the function of language in communication, managing language difficulties, intercultural disruptions, and TCK identity crisis in a global environment also relies on code-mixing, a critical sociolinguistic phenomenon. The primary objectives of the study are to look into various types of code-mixing and the reasons why people use it in the video Language Barriers, Culture Shock & TCK Identity Crisis ft. Mella Carli on the Indah G Show YouTube channel. This study used a qualitative approach, with data collected through video transcription. This study used content analysis, focusing on examining all possible types of code-mixing as defined by Muysken and the reason for using code-mixing that was argued by Hoffman. The results of this research, firstly the types of code-mixing which were divided into insertion, alternation, and congruent lexicalization. Secondly, the reasons for using code-mixing which divides into talking about a particular topic, being emphatic about something, quoting somebody else, repetition used for clarification, intentions of clarifying the speech content for the interlocutor and expressing group identity. According to the results, alternation is the most common type of code-mixing, and talking about particular topic for the reason.